Laparoscopy sigmoidectomy- an intracorporeal anastomosis for minimally invasive approach to sigmoid surgery in our center: a case report - Marwanto, Pigur Agus; Noto Nugroho, Anung (International Surgery Journal, 2024)
Rectosigmoid cancer is the 3rd high prevalence in the world and Indonesia. Surgical management is performed by resection with margins on the proximal and distal sides of the tumor. Improving optimal quality of life by minimizing complications including anastomotic leak, post-operative abscess, surgical site infection as well as decreasing time to discharge and quicker recovery. Minimally invasive ileocolic and colorectal anastomoses may be performed using intracorporeal or extracorporeal techniques. Intracorporeal laparoscopic is reported to be superior as it minimizes bleeding and serosal injuries leading to less postoperative complication of ileus and incisional hernia. Reported a case of laparoscopic sigmoidectomy with resection intracorporeal anterior anastomosis in a 68-year-old male patient with sigmoid cancer. Three trochanter port 12 mm was used subumbilical, 2 cm above anterior superior iliac spine and 5 cm under right mid clavicle line. Counter traction was performed, descending colon was pulled medially opening the plane caudally to the promontorium of the sacrum and medial to distal dissection was performed. The mesentery of the descending colon and retroperitoneum are opened, the anterior surface of Gerota’s fascia along Toldt white line to the spleen flexure. Resection for sigmoid was performed 10 cm from proximal and 5 cm from distal sigmoid tumor. Anastomosis colon descendent and rectum using endo GIA 60 mm stappled and suture the defect using V Loc 3.0, identified leaks test was negative. The specimen was extracted out using Pfannenstiel incision. Management of laparoscopic sigmoidectomy using intracorporeal anastomosis for rectosigmoid carcinoma was effective. The patient was discharged from the hospital on the 3rd day. Evaluation was performed until 2 weeks, complications during follow-up were not found, and clinical improvement was reported.